Aplikasi Model ARIMA dalam Peramalan Data Harga Emas Dunia Tahun 2010-2022 - Mohammad Abror Gustiansyah; Akbar Rizki; Berliana Apriyanti; Kenia Maulidia; Raffael Julio Roger Roa; Oksi Al Hadi; Nabila Ghoni Trisno Hidayatulloh; Wiwik Andriyani Lestari Ningsih; Andika Putri Ratnasari; Yenni Angraini (Program Studi Statistika FMIPA UNJ, 2023)
Gold investment is one of the favorite investments during the Covid-19 pandemic because the price of gold is relatively volatile but shows an increasing trend. Savvy investors investing in gold need to be able to predict future opportunities. Therefore, price estimation is needed to develop a buying and selling strategy to maximize profits. The Autoregressive Integrated Moving Average (ARIMA) model is a suitable method for predicting time series data, so the best ARIMA model will be applied for forecasting world gold prices. The best ARIMA model is selected based on the Akaike Information Criterion (AIC) and Mean Absolute Percentage Error (MAPE) criteria. Monthly world gold price data for 146 periods are applied in this study and will be used to predict gold prices for the following six periods. ARIMA (0,1,1) is the best model obtained from the analysis results, with AIC and MAPE values of 1264.731 and 11.972%, respectively. Forecasting results show that world gold prices will increase for the next periods.